Determination of udder and teat linear morphological traits in Awassi and Bafra (Chios x Karayaka) Ewes - Seker, Ibrahim; Kul, Selim; Koseman, Abdurrahman (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
This study was carried in order to evaluate the linear morphological characteristics of the udder and teats in the breeder conditions of Awassi and Bafra (Chios x Karayaka) ewes ( Ovis aries ) and to determine the udder types, lactation milk yield and the lactation period of the ewes. One hundred two Awassi and 61 Bafra ewes were included in the study. The means of the linear scores of udder depth, udder furrow, udder attachment, teat shape, teat angle and teat placement in Awassi ewes were determined as 6.10 +/- 0.27, 6.33 +/- 0.27, 4.49 +/- 0.27, 6.49 +/- 0.33, 3.98 +/- 0.29, and 1.47 +/- 0.14, respectively. The same parameters were determined as 6.31 +/- 0.28, 6.77 +/- 0.32, 5.72 +/- 0.24, 1.20 +/- 0.11, 1.72 +/- 0.26, and 1.20 +/- 0.11, respectively, in Bafra ewes. Significant differences were found between Awassi and Bafra breeds in terms of udder types ( P <0.01). The type 3 udder, suitable for milking, was determined at the highest rate in both breeds, but type 2 udder was not detected in Awassi ewes. Statistically significant differences were found between Awassi and Bafra ewes in terms of linear morphological characteristics of udder and teat, udder attachment, teat shape, teat angle and 60 th day milk yield, daily average milk yield and lactation period ( P <0.01). Lactation milk yield and lactation period were calculated as 139.85 +/- 5.31 kg and 208.53 +/- 4.471 days, respectively, in Awassi ewes and 145.91 +/- 9.97 kg and 175.23 +/- 4.635 days in Bafra ewes, respectively. As a result, in order for linear udder characteristics to be used safely as an indirect selection criterion, there is a need for studies with a higher number of ewes and to calculate the repeatability and heritability.
Determinación de rasgos morfológicos lineales de ubre y pezón en Awassi y Bafra (Quíos × Karayaka) Ovejas
Keywords: Ewe; milk yield; lactation period; linear score; teat; placement; udder shape